Efektivitas Kombinasi Massage dan Passive Stretching terhadap DOMS dan Fleksibilitas Otot Hamstring - Yohan Adi Satria; Setya Rahayu; Sandhya Kresnajati; Riki Edo Saputro (MAN Insan Cendekia Jambi, 2026)
This study examined whether massage and passive stretching reduced Delayed Onset Muscle Soreness (DOMS) and improved hamstring flexibility in Klinik Utama Satu Sehat Semarang patients. A quasi-experimental one-group pretest–posttest approach was employed with 20 purposively selected individuals. The VAS rated DOMS intensity and the Sit and Reach Test tested flexibility. The data was analysed using the Shapiro-Wilk test and paired sample t-test (α = 0.05). There was a substantial decrease in DOMS severity from 6.12 to 2.85 (p < 0.05) and an increase in hamstring flexibility from 23.40 to 30.60 cm (p < 0.05). Conclusion: Massage and passive stretching alleviate DOMS and increase hamstring flexibility.